Irish writers and their London publishers c.1884 - 1922 - Mahony, Jane (Trinity College (Dublin, Ireland). School of English, 2016)
From the mid-1880s to the First World War, the Anglophone publishing industry, centred in London, experienced an unprecedented period of significant growth and change during which interlocking structural, legal, financial, and technological developments combined to transform the literary marketplace. The same period is notable for the Irish Literary Revival and the flowering of literary output allied to rising nationalism. Drawing on the perspectives of book and publishing history, this thesis examines the intersection of these events to assess their significance for the careers of contemporary Irish writers. The research methodology employs a holistic approach by surveying the contemporary publishing industries in London and Dublin before moving to case studies based on original archival research.
Keywords: English, Ph.D.; PhD Trinity College Dublin, 2016